VESSEL DISEASES IN INFECTION COVID-19 IN PATIENTS WITHFATAL CASES - Зинаида Александровна Хохлова; Раиса Алексеевна Гилева; Татьяна Васильевна Середа; Юлия Михайловна Кириллова (Medicina v Kuzbasse, 2022)
The aim – to investigate the risk factors of fatal case in COVID-19 and to illustrate by clinical observation. The materials and methods. There has been carried out the retrospective study analysis of patients, diagnosed with fatal cases of infection COVID-19, confirmed by PCR test for detection of RNA virus SARS-Cov2 and/or by domestic tests of Vector-best for specific antibodies IgM and IgG subclasses of diagnostic level. There has been represented the self-reporting case of clinical observation. The results. All the patients have not been vaccinated. More than half of the patients are female. About 88.9 % of patients are above 60 years of age. Nearly all of the patients have got the comorbid conditions: hypertensive disease, diabetes mellitus, the chronic nervous system disorders (cerebral dysfunction, cerebrovascular disease, encephalopathy), obesity, chronic heart disease and others. There have been diagnosed the signs of chronic vessel disease of various organs (atherosclerosis, diabetic angiopathy) in most of patients. The acute vascular disorders (vasculopathy, microthrombosis, destructive thrombovasculitis) have been detected in internals in all patients.